Financial incentives for smoking cessation in pregnancy: randomised controlled trial - Tappin, David; Bauld, Linda; Purves, David; Boyd, Kathleen; Sinclair, Lesley; MacAskill, Susan; McKell, Jennifer; Friel, Brenda; McConnachie, Alex; Caestecker, Linda de; Tannahill, Carol; Radley, Andrew; et al. (BMJ Publishing Group, 2015)
Objective: To assess the efficacy of a financial incentive added to routine specialist pregnancy stop smoking services versus routine care to help pregnant smokers quit.